Strong Photospheric Heating Indicated by Fe i 6173 Å Line Emission during White-light Solar Flares - Samuel Granovsky; Alexander G. Kosovichev; Viacheslav M. Sadykov; Graham S. Kerr; Joel C. Allred (The Astrophysical Journal, 2025)
Between 2017 and 2024, the Helioseismic and Magnetic Imager (HMI) on board the Solar Dynamics Observatory has observed numerous white-light solar flares (WLFs). HMI spectropolarimetric observations of certain WLFs, in particular the X9.3 flare of 2017 September 6, reveal one or more locations within the umbra or along the umbra/penumbra boundary of the flaring active region where the Fe I 6173 Å line briefly goes into full emission, indicating significant heating of the photosphere and lower chromosphere. For five flares featuring Fe I 6173 Å line-core emission, we perform spectropolarimetric analysis using HMI 90 s cadence Stokes data. For all investigated flares, line-core emission is observed to last for a single 90 s frame and is either concurrent with or followed by an increase in the line continuum intensity lasting one to two frames (90–180 s). Additionally, permanent changes to the Stokes Q , U , and/or V profiles were observed, indicating long-lasting nontransient changes to the photospheric magnetic field. These emissions coincided with local maxima in hard X-ray emission observed by Konus-Wind, as well as local maxima in the time derivative of soft X-ray emission observed by GOES 16-18. Comparison of the Fe I 6173 Å line profile synthesis for the ad hoc heating of the initial empirical VAL-S umbra model and quiescent-Sun (VAL-C-like) model indicates that the Fe I 6173 Å line emission in the white-light flare kernels could be explained by the strong heating of initially cool photospheric regions.